Receptors from Glucocorticoid-Sensitive Lymphoma Cells and Two Classes of Insensitive Clones: Physical and DNA-Binding Properties - Yamamoto, Keith R. (1974)
Mouse lymphoma tissue culture cells (S49.1A) are normally killed by dexamethasone, a synthetic glucocorticoid hormone. Dexamethasone-resistant clones have been selected from this line, some of which retain the ability to specifically bind dexamethasone. Addition of [(3)H]dexamethasone to cultures, followed by cell fractionation, reveals that the nuclear transfer of hormone-receptor complexes in some of these variant clones is deficient (nt(-)), while others show increased nuclear transfer (nt(i)) relative to the parental line. Two independently selected members of each class have been studied here, in an effort to elucidate the molecular determinants involved in the receptor-nucleus interaction in vivo. The labeled receptors in cell-free extracts bind to DNA-cellulose, but only after previous incubation of the extract at 20°, similar to the treatment required for cell-free interaction of receptors with nuclei. More importantly, the apparent DNA-binding affinity of the nt(-) receptors is lower than the wild type, whereas the nt(i) receptors bind DNA with an affinity higher than the parental molecules. The parallelism of nuclear and DNA binding, together with the observations that the receptors from the variants have sedimentation properties different from the wild-type cells, lead us to conclude that (i) these variants may contain altered receptor molecules and (ii) DNA is probably the primary nuclear binding site for steroid receptors in vivo.